The Urgency of Learning Fiqh Ubudiyah With The Book of Fathul Qarib - Fahmi Al Mahfudh; Fatkhurrahman Fatkhurrahman; Sri Jumini; Anaas Tri Ridlo Dina Yuliana (Al-Misbah (Jurnal Islamic Studies), 2023)
This study aims to reveal the urgency of learning fiqh ubudiyah using the Book of Fathul Qarib in Islamic boarding schools Alhikmah 2 Benda Sirampog Brebes. Fiqh ubudiyah refers to the understanding and application of Islamic laws in the context of devotion and obedience performed by individual Muslims to Allah Almighty. The Book of Fathul Qarib was chosen as one of the reference sources because it provides a deep understanding of the principles of fiqh and the procedures of worship in Islam. This research uses a qualitative method with a case study approach in several Islamic boarding schools that have adopted the learning of fiqh ubudiyah using the Book of Fathul Qarib. Data were collected through observation, interviews, and analysis of documents related to the curriculum and teaching methods used. The results showed that learning fiqh ubudiyah with the Book of Fathul Qarib has significant urgency in Islamic boarding schools. This learning helps students in understanding and apply Islamic laws in everyday life with the perspective of ubudiyah, which is a form of devotion and obedience to Allah SWT. The use of Kitab Fathul Qarib as a reference source also allows students to learn the principles of fiqh comprehensively, including the correct worship procedures. In addition, learning fiqh ubudiyah with the Book of Fathul Qarib also has other positive impacts, such as increasing the spiritual and moral awareness of Alhikmah 2 Benda Sirampog Brebes students, strengthening ties with true Islamic teachings, and forming a noble and responsible character. This study recommends that other Islamic boarding schools also adopt fiqh ubudiyah learning by using the Book of Fathul Qarib as an effort to enrich learning methods and strengthen the religious foundation of santri. It is also expected that further research involving respondents will be broader and cover various aspects of the influence of fiqh ubudiyah learning in the context of Islamic education in Islamic boarding schools.